Comparison of prognosis and outcomes of catheter ablation versus drug therapy in patients with atrial fibrillation and stable coronary artery disease: A prospective propensity‐score matched cohort study - Cui, Yi‐Kai; Dong, Jian‐Zeng; Du, Xin; Hu, Rong; He, Liu; Jia, Chang‐Qi; Li, Xu; Wu, Jia‐Hui; Yu, Rong‐Hui; Long, De‐Yong; Ning, Man; Sang, Cai‐Hua; et al. (Clinical cardiology (Mahwah, N.J.), 2021)
Background Atrial fibrillation (AF) and stable coronary artery disease (SCAD) frequently coexist. Hypothesis To investigate the prognosis of catheter ablation versus drug therapy in patients with AF and SCAD. Methods In total, 25 512 patients with AF in the Chinese AF Registry between 2011 and 2019 were screened for SCAD. 815 patients with AF and SCAD underwent catheter ablation therapy were matched with patients by drug therapy in a 1:1 ratio. Primary end point was composite of thromboembolism, coronary events, major bleeding, and all‐cause death. The secondary endpoints were each component of the primary endpoint and AF recurrence. Results Over a median follow‐up of 45 ± 23 months, the patients in the catheter ablation group had a higher AF recurrence‐free rate (53.50% vs. 18.41%, p < .01). In multivariate analysis, there was no significant difference between the strategy of catheter ablation and drug therapy in primary composite end point (adjusted HR 074, 95%CI 0.54–1.002, p = .0519). However, catheter ablation was associated with fewer all‐cause death independently (adjusted HR 0.36, 95%CI 0.22–0.59, p < .01). In subgroup analysis, catheter ablation was an independent risk factor for all‐cause death in the high‐stroke risk group (adjusted HR 0.39, 95%CI 0.23–0.64, p < .01), not in the low‐medium risk group (adjusted HR 0.17, 95%CI 0.01–2.04, p = .17). Conclusions In the patients with AF and SCAD, catheter ablation was not independently associated with the primary composite endpoint compared with drug therapy. However, catheter ablation was an independent protective factor of all‐cause death